2016
DOI: 10.3390/w8070294
|View full text |Cite
|
Sign up to set email alerts
|

Stormwater Management: Calculation of Traffic Area Runoff Loads and Traffic Related Emissions

Abstract: Metals such as antimony, cadmium, chromium, copper, lead, nickel, and zinc can be highly relevant pollutants in stormwater runoff from traffic areas because of their occurrence, toxicity, and non-degradability. Long-term measurements of their concentrations, the corresponding water volumes, the catchment areas, and the traffic volumes can be used to calculate specific emission loads and annual runoff loads that are necessary for mass balances. In the literature, the annual runoff loads are often specified by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…The calculated micropollutant loads in untreated road runoff are summarized in Table 3. The median annual Cu load per road surface area (851 g/ha/year) is high compared to most values issued from a review of annual traffic area runoff loads (median 355, with values ranging from 34-3780 g/ha/year), while that of Zn (2360 g/ha/year) is slightly below the median (2600 g/ha/year) issued from the same data set [31]. Table 3.…”
Section: Micropollutant Load In Road Runoffmentioning
confidence: 78%
“…The calculated micropollutant loads in untreated road runoff are summarized in Table 3. The median annual Cu load per road surface area (851 g/ha/year) is high compared to most values issued from a review of annual traffic area runoff loads (median 355, with values ranging from 34-3780 g/ha/year), while that of Zn (2360 g/ha/year) is slightly below the median (2600 g/ha/year) issued from the same data set [31]. Table 3.…”
Section: Micropollutant Load In Road Runoffmentioning
confidence: 78%
“…12,13 It has been known for decades that urban stormwater is a contributor to the impairment of water quality. 14 Thus, monitoring and management programs have focused on conventional stormwater pollutants such as total suspended solids (TSS), [15][16][17] nutrients, 15,18 pathogens, [19][20][21] metals, [15][16][17][18]22,23 polycyclic aromatic hydrocarbons (PAHs), 17,[24][25][26] polychlorinated biphenyls, 27 and certain pesticides. 28,29 While stormwater research has long concentrated on particle-associated pollutants, a review article by LeFevre et al 18 highlighted the importance of dissolved stormwater pollutants (mainly nutrients, toxic metals, and hydrocarbons) and identified a major lack of knowledge about hyphil-TrOCs.…”
Section: Introductionmentioning
confidence: 99%
“…The main sources of emitted Polycyclic Aromatic Hydrocarbons (PAH) were vehicle exhaust gases, followed by tire wear, motor lubricant oils, road surface wear, and brake linings. Contributions from surrounding land use, such as agriculture, industrial, or urban areas, are also acknowledged (e.g., [32]). Solids or dust found in road pavement are originated from distinct sources and materials: pavement wear; construction sites or rehabilitation works; atmospheric fallout; anthropogenic wastes; and vehicles components deterioration-with tire wear being a relevant source [21,33,34].…”
Section: The Road Pavement As a Sink And Source Of Road Runoff Pollut...mentioning
confidence: 99%
“…It has been demonstrated that the discharge of even small concentrations of road runoff pollutants can lead to impacts in confined water bodies (e.g., [47]). It is not just the total concentration that must be evaluated; the fraction of pollutants present in dissolved or particulate form is relevant for impact evaluation and the design of treatment systems [32,48,49]. Several countries have already characterized national road runoff constitution and know which are the most relevant pollutants.…”
Section: The Road Pavement As a Sink And Source Of Road Runoff Pollut...mentioning
confidence: 99%